Oswald's Marketing Semiotics Analysis: Cultural Elements in Marketing Communication at the "Bajawa Flores NTT" Café - Panjaitan, Tetti Nauli; Winarko, Hilarius Bambang; Yudhi, Lim; Felita, Della (Journal of Public Representative and Society Provision, 2025)
This study analyzes how Flores' cultural elements are used as a marketing communication strategy at Kafe Bajawa. Using a qualitative approach and Oswald’s marketing semiotics analysis, the research explores the meanings embedded in cultural elements such as Komodo statues, woven fabrics, Sasando musical instruments, photographs of Flores residents, a map of Flores Island, and the collaboration of traditional music with modern genres. Data were collected through direct observation of both exterior and interior decorations, as well as customer interviews to understand their responses to the presented cultural elements. The findings indicate that Flores' cultural elements play a significant role in shaping the café's identity and appeal. Analysis based on Consumer Brandscape shows that cultural signs create an authentic and unique impression, while emotional territories indicate that these cultural elements build emotional connections with customers through a comfortable and dynamic atmosphere. There is no cultural tension between traditional and modern elements; instead, they harmoniously blend, particularly in interior design and the music experience. From the perspective of cultural categories, Kafe Bajawa successfully positions itself as a venue that embodies Flores' cultural heritage in a modern context. Data triangulation through customer interviews confirms that the displayed cultural elements reinforce the café’s image as a space rich in local identity while remaining comfortable for an urban audience. The success of this strategy lies in balancing culture and modernity, creating an engaging experience that fosters customer loyalty.